Multi-region investigation of ‘man’ as default in attitudes - Curtis Edward Phills; Jeremy K. Miller; Erin M. Buchanan; Amanda Williams; Chanel Meyers; Elizabeth R. Brown; Janis Zickfeld; Selina Volsa; Stefan Stieger; Elisabeth Oberzaucher; Vinka Mlakic; Martin Vasilev; et al. (PLoS ONE, 2025)
Previous research has studied the extent to which men are the default members of social groups in terms of memory, categorization, and stereotyping, but not attitudes which is critical because of attitudes’ relationship to behavior. Results from our survey (N > 5000) collected via a globally distributed laboratory network in over 40 regions demonstrated that attitudes toward Black people and politicians had a stronger relationship with attitudes toward the men rather than the women of the group. However, attitudes toward White people had a stronger relationship with attitudes toward White women than White men, whereas attitudes toward East Asian people, police officers, and criminals did not have a stronger relationship with attitudes toward either the men or women of each respective group. Regional agreement with traditional gender roles was explored as a potential moderator. These findings have implications for understanding the unique forms of prejudice women face around the world.